A propriedade fiduciária imobiliária: aspectos gerais e registrários - Clápis, Alexandre Laizo (2010)
The purpose of this work is to review general issues related to a type of security, the fiduciary ownership of real estate (propriedade fiduciária imobiliária) associated with practical aspects of its registration. The fiduciary ownership was introduced in the Brazilian legal system by Federal Law No. 9,514/1997, although it has been being used to secure the financing of durable goods for a long time. After the issuance of such law, within the scope of the Brazilian Real Estate Financing System SFI, the fiduciary ownership of real estate emerged as an alternative to the weakened Brazilian Housing System SFH. The Brazilian real estate market benefited from the introduction of a new type of fiduciary security. In particular because the mechanisms available to the creditor to recover its credit were expedited and improved with the sale of the property at extrajudicial public auctions, this is to say, with the possibility of the fiduciary/trustee (fiduciário) to recover the amount financed with no need to file a judicial execution proceeding that is knowingly more time consuming and involves higher costs. To understand the current features of the Brazilian fiduciary ownership of real estate, one must return to the origin of the institute, particularly to the fidúcia (trust) of Roman Law and the one that has appeared in Germanic Law because one has served itself from the failure of the other in an attempt to improve its structure and introduce, in the German fiduciary relationship, the resolvable condition resulting from the law rather than from the fiduciary s will, as it happened in Roman Law. However, in any of those origins, it is possible to notice that the special attractive of this type of security is the transfer of the title to the fiduciary, so that the security is created on a creditor s asset. Because of the increasing use of this type of security, Brazilian courts have already had the opportunity to pronounce on fundamental aspects such as the constitutionality of the extrajudicial enforcement of the security consisting of the fiduciary ownership of real estate in other words, the mandatory public auctions, in case of default of the fiduciary agent (fiduciante) does not violate constitutional commandments of access to courts and full defense and, similarly, the structure of reimbursement of the fiduciary and the fiduciary agent, in case there is any balance after the sale at an extrajudicial public auction does not violate Article 53 of the Brazilian Consumers Defense Code